PENERAPAN METODE PEMBELAJARAN DALAM KURIKULUM MERDEKA DI MADRASAH - salma, suci nurul jannah; Nadlrah Naimi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to identify and obtain information about how the independent curriculum is implemented in madrasas and secondary schools. This article was written using a literature review method or literature study, namely combining several quotations from available scientific works. So that readers gain a new understanding of what independent curriculum is and how it is implemented in real terms. The results of this research show that the implementation of the curriculum in driving schools has been carried out optimally and is ongoing, although in its implementation there are still many shortcomings and obstacles. The key to success in implementing the curriculum in driving schools is the principal and teachers, the teachers must have the will to make changes. The school principal as a leader must be able to change the mindset of the Human Resources in the school to be willing to make changes so that the  independ curriculum can be implemented.The Merdeka Curriculum as an alternative curriculum overcomes learning setbacks during the pandemic which gives "Freedom to Learn" freedom to learning implementers, namely teachers and school principals, in preparing, implementing the learning process and developing curriculum in schools paying attention to students' needs and potential.